Genetic and environmental factors in interstitial lung diseases: current and future perspectives on early diagnosis of high-risk cohorts - Stanel, Stefan Cristian; Callum, Jack; Rivera-Ortega, Pilar (Frontiers in Medicine, 2023)
Within the wide scope of interstitial lung diseases (ILDs), familial pulmonary fibrosis (FPF) is being increasingly recognized as a specific entity, with earlier onset, faster progression, and suboptimal responses to immunosuppression. FPF is linked to heritable pathogenic variants in telomere-related genes (TRGs), surfactant-related genes (SRGs), telomere shortening (TS) and early cellular senescence. Telomere abnormalities have also been identified in some sporadic cases of fibrotic ILD. Air pollution and other environmental exposures carry additive risk to genetic predisposition in pulmonary fibrosis. We provide a perspective on how these features impact on screening strategies for relatives of FPF patients, interstitial lung abnormalities, ILD multi-disciplinary (MDT) discussion, and disparities and barriers to genomic testing. We also describe our experience with establishing a familial interstitial pneumonia (FIP) clinic and provide guidance on how to identify patients with telomere dysfunction who would benefit most from genomic testing.